Lip reposition surgery: A new call in periodontics - Tejal Sheth; Shilpi Shah; Mihir Shah; Ekta Shah (Wolters Kluwer Medknow Publications, 2013)
"Gummy smile" is a major concern for a large number of patients visiting the dentist. Esthetics has now become an integral part of periodontal treatment plan. This article presents a case of a gummy smile in which esthetic correction was achieved through periodontal plastic surgical procedure wherein a 10-12 mm of partial-thickness flap was dissected apical to mucogingival junction followed by approximation of the flaps. This novel technique gave excellent post-operative results with enormous patient satisfaction. This surgical chair-side procedure being one of its kinds with outstanding results is very rarely performed by Periodontists. Thus, a lot of clinical work and literature review with this surgical technique is required. To make it a routine surgical procedure this technique can be incorporated as a part of periodontal plastic surgery in the text. Hence, we have put forward experience of a case with critical analysis of the surgical technique including the limitations of the technique.